The Influence of Digital Native Media Utilization and Network Homogeneity on Creative Expressive Ability in an Open Innovation Paradigm - Eun Joo Kim (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study conducted a digital content development class that conform to the interests of the education students. We analyzed their creative expressive ability before and after participating in the said class. Furthermore, this study evaluated how media utilization and network homogeneity among the characteristics of digital natives affect their creative expressive ability. The subjects of the study are 320 students from four-year E universities in Gyeonggi-do. The results revealed that the digital content development class proposed in this study can be fully utilized as a class model that reflects the needs of the current generation and invigorates the curriculum for digital nativization.